ABOUT FEATURES OF PHRASEOLOGICAL UNITS CONTAINING NUMBERS (BY THE EXAMPLE OF THE AZERBAIJANI AND ENGLISH LANGUAGES) - Mursalov, R.J (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The study of phraseological units is one of the relevant aspects of modern linguistics. It has not yet been precisely determined whether proverbs, sayings and winged words can be included in phraseological units. They are attributed to both stable (phraseological units) and unstable phrases. The analysis of phraseological units containing quantitative indicators is also important. It is known that such units occupy an important place in the vocabulary of both English and Azerbaijani. Such phrases expand the semantic capabilities of the language. Phraseological units with the number "6" are used in each of these languages. The article discusses the structural and semantic features of such phrases. It is determined that the differences are associated with the general characteristics of the development of each of the languages. Attention is also drawn to such an interesting point that most researchers of phraseological units in the Azerbaijani and English languages consider idioms in a narrow sense, while a smaller part explores idioms and phraseological phrases in a broader sense, thereby referring even terminological phrases with emotionally expressive phrases and phrases load. All this inevitably contributes to the formation of a number of questions about phraseology, which still have not found their solution.